Strategi Dalam Pemberantasan Tindak Pidana Korupsi di Lingkungan PT Waskita Karya (The Digest: Journal of Jurisprudence and Legisprudence, 2022)
State-Owned Enterprises as a government tool in seeking profit in running their business in managing funds from capital receipts from the government have a great potential for corrupt practices. Therefore, PT Waskita Karya in suppressing and taking preventive steps for corruption by implementing preventive efforts in preventing at Waskita Karya Group with a Situational Prevention Crime approach that focuses on internal and external supervision and narrows space in areas prone to corruption. Then improve the quality of human resources with integrity and quality. In addition to a preventive approach, a repressive approach by taking an approach that focuses on asset recovery due to losses from corruption through one of the civil law instruments, civil forfeiture as regulated in the Anti-Corruption Law.